Dos 365 dias do ano, em pelo menos 60, eu sangro! um estudo sobre estigmatização e vulnerabilidades no consumo de produtos de gestão menstrual de mulheres de baixa renda - (:unkn) unknown (Universidade Federal do Pampa, 2025)
Menstruation is a natural biological process that occurs every month for approximately 40 years and impacts a large portion of the population. In view of this, the general objective of this study is to understand how low-income women deal with stigmatization and double vulnerability in the consumption of menstrual management products. To this end, a qualitative study was conducted, based on 20 narrative interviews with low-income women, as well as notes in a field diary and the use of the photo-elicitation technique. Among the main results, it is worth highlighting that the consumption of menstrual products is permeated by stigmas deeply rooted in society, manifested through menstrual bullying, shame, silence and concealment of one's own body. Such practices reinforce a culture of misogyny, machismo, patriarchy and religious taboos, impacting generations. Gender vulnerability manifests itself in the restriction of daily activities, such as leisure and work, due to pain, insecurity with leaks and social stigmas. Socioeconomic vulnerability is evident in the difficulty of accessing menstrual products, forcing women to improvise with inadequate items, such as bread crumbs and plastic bags, and to opt for cheaper and more uncomfortable brands. The main contributions of this study consist of understanding the consumption of menstrual management products from the perspective of vulnerability and stigma, highlighting the intersectional impacts of gender inequality and socioeconomic precariousness. In addition to understanding the impact of stigmatization on consumption practices, by highlighting how socially constructed meanings around menstruation shape perceptions, behaviors and choices related to menstrual management products. In the field of Administration, the research challenges the invisibility of menstruation as an object of research, by demonstrating how organizational practices, consumer relations and public policy formulations are permeated by menstrual stigmas. As a practical contribution, the study offers support for more effective public policies that recognize menstruation as a relevant social marker.
I bleed at least 60 of the 365 days of the year! A study on stigmatization and vulnerabilities in the consumption of menstrual management products by low-income women
Keywords: Estigma; Vulnerabilidade; Gênero; Baixa renda; Produtos de gestão menstrual; Stigma; Vulnerability; Gender; Low income; Menstrual management products; CIENCIAS SOCIAIS APLICADAS